Synergetically Selective Toluene Sensing in Hematite‐Decorated Nickel Oxide Nanocorals. Issue 3 (27th January 2017) - Suh, Jun Min; Shim, Young‐Seok; Kim, Do Hong; Sohn, Woonbae; Jung, Youngmo; Lee, Seon Yong; Choi, Seokhoon; Kim, Yeon Hoo; Jeon, Jong‐Myeong; Hong, Kootak; Kwon, Ki Chang; Park, Seo Yun; et al.
Abstract : The decoration of p ‐type nickel oxide (NiO) with n ‐type hematite (α‐Fe2 O3 ) to achieve vertically ordered 1D nanostructures is an attractive strategy to enhance gas sensing properties. Herein, the authors report a facile method for α‐Fe2 O3 decoration of the whole surface of vertical NiO nanorods. An NiO/Fe heterostructure is deposited in multiple steps using a glancing angle deposition method, which is followed by the oxidation of Fe into α‐Fe2 O3 . Thermally agglomerated α‐Fe2 O3 nanoparticles are uniformly distributed on the whole surface of the NiO nanorods. Due to the α‐Fe2 O3 decoration, the NiO nanorods exhibit a coral‐like rough surface and, more interestingly, their preferential crystallographic orientation changed from (111) to (200). Compared to bare NiO nanorods, the α‐Fe2 O3 ‐decorated NiO nanocorals exhibit a 45.4 times higher response to 50 ppm toluene (C7 H8 ) at 350 °C. Their theoretical detection limit for C7 H8 is calculated to be ≈22 ppb. The observed unprecedented synergetic effects of α‐Fe2 O3 ‐decorated NiO nanocorals for the extremely selective C7 H8 sensing, as well as their facile synthetic route, establish a new perspective on heterostructured metal oxide 1D nanostructures for selective gas sensing. Abstract : Highly selective toluene sensing of hematite (α‐Fe2 O3 )‐decorated nickel oxide (NiO) nanocorals is achieved by synergetic effects of α‐Fe2 O3 decoration on NiO nanorods. The structural effects, formation of p – n junctions, catalytic role of α‐Fe2 O3, and crystallographic orientation change in NiO synergetically enhance the gas sensing performance of α‐Fe2 O3 ‐decorated NiO nanocorals.